DEVELOPMENT OF TETRAETHYLENEPENTAMINE-FUNCTIONALIZED MESOPOROUS SILICA FORCARBON DIOXIDE ADSORPTION - LEE , XIN YING (2020)
Michigan State University-2 (MSU-2)is very potential CO2adsorbent due to its three-dimensional (3D) wormhole-like framework structure which is highly interconnected. MSU-2 was synthesizedvia solution precipitation method and functionalized via wet impregnation method using different loading (20, 30, 40, 50 and 60 wt%)of tetraethylenepentamine (TEPA) to enhance the CO2adsorption capacity. The effect of different TEPA loading on the CO2adsorption capacity of the adsorbent samples was investigated via gas adsorption studies conducted at 40 °C and 1 bar. Besides, the adsorbents were studied in term of morphologies, pore structures, pore characteristics, elemental compositions, crystallographic structures, functional groups and chemical bonding as well as thermal stabilities